As ilustrações de Zé Manel para as narrativas de Luísa Ducla Soares: inovação e experimentalismo - Silva, Sara Raquel Reis da (2019)
The present study takes up and analyses three important books by Luísa Ducla Soares (1939-), namely A História da Papoila (1972), O Soldado João (1973) and O Ratinho Marinheiro (1973), which that have in common a visual composition by the artist Zé Manel (1944-2019). The intention is to prove the innovative character, not only of the verbal text, but also, and especially, of illustrations, taking into account the context of creation, that is, still in the Estado Novo period (1926-1974). Besides seeking to clarify the semantic relations between literary discourse and illustrative discourse, we attempt to elucidate some of the aesthetic singularities of Zé Manel’s versatile, perspicacious, attentive, sensitive and very personal iconic visual work, an indispensable personality (also) of the History of Portuguese Illustration for Children.